2009
DOI: 10.1128/jb.01630-08
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the ParG Segregation Protein to Different Affinity DNA Sites

Abstract: The segrosome is the nucleoprotein complex that mediates accurate plasmid segregation. In addition to its multifunctional role in segrosome assembly, the ParG protein of multiresistance plasmid TP228 is a transcriptional repressor of the parFG partition genes. ParG is a homodimeric DNA binding protein, with C-terminal regions that interlock into a ribbon-helix-helix fold. Antiparallel ␤-strands in this fold are pre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…A 466 bp DNA fragment containing the promoter region of the tubRZ-Bs operon was amplified from plasmid pXK with unlabelled primer # 71 and 59-biotinylated primer # 72. Footprinting reactions were performed as described by Zampini et al (2009). Briefly, reactions containing biotin-labelled DNA (5 nM) and TubR-Bs (0.1-2.0 mM) were mixed in 50 ml EMSA binding buffer and incubated for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A 466 bp DNA fragment containing the promoter region of the tubRZ-Bs operon was amplified from plasmid pXK with unlabelled primer # 71 and 59-biotinylated primer # 72. Footprinting reactions were performed as described by Zampini et al (2009). Briefly, reactions containing biotin-labelled DNA (5 nM) and TubR-Bs (0.1-2.0 mM) were mixed in 50 ml EMSA binding buffer and incubated for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The parH centromere that is recognized by ParG comprises a set of degenerate tetramer motifs separated by AT-rich spacers (33). ParG also is a transcriptional repressor of the parF-parG cassette which is achieved by binding to a second array of tetramer boxes upstream of the genes (38). Like other RHH proteins, ParG recognizes DNA via the antiparallel ␤-strands that comprise the ribbon element.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive sequence variability in the ribbon element permits diverse RHH proteins to interact with discrete DNA sequences (37). In the case of ParG, the ribbon recognizes an array of degenerate tetramer boxes interspersed by AT-rich spacers both in the parH centromere, and at the operator site during transcriptional repression of the parF-parG genes (33,38).…”
mentioning
confidence: 99%
“…This segregation stability was shown to require a type Ib partition system encoding two proteins, the 22-kDa ParF protein and the 8.6-kDa ParG protein (20,22). Subsequently, it was demonstrated that ParG functions as the CBP that binds cooperatively to the parH centromere site to form a partition complex, which recruits ParF (23,24). ParG plays a second critical role in partition by stimulating the ATPase activity of ParF.…”
mentioning
confidence: 99%